Albanian GDP and It’s Components by Sectors - Fejzo, Jeta (Mediterranean Journal of Social Sciences, 2012)
This paper covers a presentation of macroeconomics figures focused on Albanian GDP. The aim of the paper is to determinehow the GDP components and sectors play on overall Albanian GDP. The study focused on historical and actual data in order to specifythe role of each component and sector on the impact over Albanian GDP. Also the research has affected the informal economy and itsimpact on GDP The Empirical findings of the study are based on data taken from official sources such as BoA, INSTAT, IMF, WorldBank. The graphs indicate the prolonged influence of the sectors over GDP and the forecast for the coming years. The data used in thispaper belong to the period 1998-2009.After making the analysis, using regression as a methodology, must determine components ofGDP and which one is the most important one for the Albania GDP.